The Influence of Learning Assistance and Parents’ Educational Background on Children’s Learning Motivation - Setiarini, Ani; Minsih (International Journal of Elementary Education, 2022)
The role of parents greatly affects the motivation and learning achievement of children to be able to create children's learning motivation. One way that parents can do is to accompany their children and prepare supporting facilities for learning activities at home. This study aims to analyses the impact of the existence of learning assistance and the educational background of parents on children’s learning motivation. In this research, the method use is descriptive quantitative with survey design. The research subjects were students in grades IV – VI, with a total of 30 students as respondents. The instrument that used in this study is questionnaire. The steps taken in this study consisted of several stages such as making questionnaires, distributing questionnaires, and processing data with prerequisite tests and hypothesis testing using the SPSS application. The data analysis used for this research is a prerequisite test with validity, reliability, normality, and linearity tests. From the data analysis of this study, the result of the validity test of all valid and reliable questions were obtained, the normality test with a value sig. 0.200, a linearity test with a value of sig. 0.166 between X1 and Y and 0.720 between X2 and Y, and hypothesis testing using the t-test with a value of sig. 0.000, f-test with a value of sig. 0.000, which means the hypothesis is accepted and the determination of deficiency is 58.2%. Then there is the influence of mentoring and parents’ educational background on learning motivation.